Reframing the early childhood curriculum educational imperatives for the future / Jane M. Page. - Page, Jane M., 1963- (Futures and education series., 2000)
Argues that pre-school children have a less apprehensive view of the future than adolescents and that an effective programme in the early years can counteract the difficulties youths experience.